2008
DOI: 10.1080/15513810802077586
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive Dermopathy: Report and Review

Abstract: Restrictive dermopathy is a rare autosomal recessive disorder characterized by extreme tautness of the skin causing restricted intrauterine movement and a fetal akinesia deformation sequence. It is uniformly mostly neonatally fatal. The diagnostic findings are skin tautness with near absence of the dermal elastic fibers, usually with no or only minor anomalies of the internal organs. The exact pathogenetic mechanisms are still not known. Fewer than 50 cases have been reported. We report on a case of restrictiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 18 publications
(26 reference statements)
0
17
0
Order By: Relevance
“…Dermal adnexae are distorted and poorly developed, and epidermal retia may be flattened. The underlying subcutis is unaffected 13–15 . These findings, when coupled with clinical features, are diagnostic.…”
Section: Congenital Disordersmentioning
confidence: 82%
See 2 more Smart Citations
“…Dermal adnexae are distorted and poorly developed, and epidermal retia may be flattened. The underlying subcutis is unaffected 13–15 . These findings, when coupled with clinical features, are diagnostic.…”
Section: Congenital Disordersmentioning
confidence: 82%
“…Most infants also show widened cranial sutures, a small pinched nose, low‐set ears, rocker‐bottom feet, microstomia, scaly skin, bone deformities, and respiratory insufficiency. Death occurs early in the neonatal period 13,14 …”
Section: Congenital Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…While the locally thickened skin with nodules, joint contractures, and some other characteristics overlapped with several connective tissue disorders (Table 1), 1–25 the full spectrum of the phenotypic features appeared inconsistent with any known fibrotic and contractural disease and revealed a previously unrecognized fibrotic disorder.…”
Section: Case Reportmentioning
confidence: 99%
“…Restrictive dermopathy (OMIM 275210) is a rare lethal genetic disorder that is characterized by congenital tautness of the skin causing fetal akinesia or hypokinesia deformation sequence, characteristic facial features (small mouth, small pinched nose, and micrognathia), bone mineralization defects including thin, dysplastic clavicles, and pulmonary hypoplasia. Patients usually die immediately after birth or may struggle to survive for several weeks (1). Navarro et al (2) recently reported that restrictive dermopathy is either a primary or a secondary laminopathy, caused by dominant de novo mutations in the lamin A gene ( LMNA ) or, more frequently, recessive null mutations in the gene coding the endoprotease ZMPSTE24.…”
mentioning
confidence: 99%